Basic amino acids flanking the zinc finger of Moloney murine leukemia virus nucleocapsid protein NCp10 are critical for virus infectivity. - Housset, V (1993)
Nucleocapsid (NC) protein NCp10 of Moloney murine leukemia virus is encoded by the 3' domain of gag and contains a zinc finger surrounded by basic amino acids. During virion assembly, NC protein is necessary for core formation and the NC zinc finger is required for the packaging of the genomic RNA dimer. In vitro NCp10 has RNA-binding and -annealing activities critical for virus infectivity, since NCp10 promotes dimerization of viral RNA containing the Psi packaging element and annealing of replication primer tRNA(Pro) to the initiation site of reverse transcription (primer-binding site). To investigate the role of the basic amino acids flanking the NCp10 zinc finger, neutral residues were substituted for the basic amino acids and the effects of these mutations in vivo on virus assembly and infectivity and in vitro on the RNA-annealing activity of NCp10 were analyzed. Here we report that the substitution of 1 or 2 neutral amino acids for the basic residues did not impair the production of mature virions but that infectivity was either moderately or strongly attenuated. When more than 2 basic residues were replaced by neutral amino acids, viruses were poorly infectious because of a severe defect in genomic RNA dimer packaging and initiation of reverse transcription. In vitro NCp10-derived peptides with similar mutations were chemically synthesized and were found to be either fully or partially active or completely inactive. These data indicate that the basic residues flanking the zinc finger of NCp10 are required for the production of infectious Moloney murine leukemia virus virions.